Nonlinear Behavior of a Micro-resonator with Electrostatic Force on Both Sides that is Described by a Duffing Type Oscillator - Laskaridis, L.; Maaita, J.O.; Meletlidou, E. (Discontinuity, Nonlinearity, and Complexity, 2026)
A Duffing type oscillator simulates a micromechanical resonator with electrostatic force on both sides. The system, concerning the amplitude of the external excitation and the damping parameter, has rich dynamics that contain regular (periodic and semi- periodic) and chaotic oscillations. Melnikov’s function proves the existence of homoclinic chaos.